Rearrangement of immunoglobulin gamma 1-chain gene and mechanism for heavy-chain class switch. - Kataoka, T (1980)
Cloning and nucleotide sequence determination suggest that the rearranged gamma 1-chain gene in a gamma 1-chain-producing myeloma a-pears to be formed by the recombination between the 5' flanking regions of the gamma 1- and mu-chain genes of undifferentiated cells. The recombination site is distinct from the putative J region and is a novel region that we call the S region. We have extended our previous model that explains the heavy-chain class switching by two or more successive recombination events.